Treatment-enhanced paired action contributes substantially to change across multiple health behaviors: secondary analyses of five randomized trials - Yin, Hui-Qing (Springer-Verlag, 2013)
The dominant paradigm of changing multiple health behaviors (MHBs) is based on treating, assessing, and studying each behavior separately. This study focused on individuals with co-occurring baseline health-risk behavior pairs and described whether they changed over time on both or only one of the behaviors within each pair. Data from five randomized trials of computer-tailored interventions (CTIs) that simultaneously treated MHBs were analyzed. The differences between treatment and control proportions that achieved paired action and singular action at 24 months follow-up, and the proportional contribution of paired action to overall change on each behavior, were assessed across 12 behavior pairs (including energy balance, addictive, and appearance-related behaviors). CTIs consistently produced more paired action across behavior pairs. Paired action contributed substantially more to the treatment-related outcomes than singular action. Studying concurrent changes on MHBs as demonstrated allows the effect of simultaneously treating MHBs to be assessed.